2016
DOI: 10.1007/s13277-016-5347-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-490 regulates lung cancer metastasis by targeting poly r(C)-binding protein 1

Abstract: Lung cancer remains a leading cause of cancer-related mortality, with metastatic progression remaining the single largest cause of lung cancer mortality. Hence, it is imperative to determine reliable biomarkers of lung cancer prognosis. MicroRNA-490-3p has been previously reported to be a positive prognostic biomarker for hepatocellular cancer. However, its role in human lung cancer has not yet been elucidated. Here, we report that hsa-miR-490-3p expression is significantly higher in human lung cancer tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Lung cancer is the most common cause of cancer-related mortality both for men and women worldwide, with an estimated of 1.4 million deaths per year (1,2). There are two principal forms of lung cancer: Small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common cause of cancer-related mortality both for men and women worldwide, with an estimated of 1.4 million deaths per year (1,2). There are two principal forms of lung cancer: Small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, miRNAs play roles in various cellular processes, including cell proliferation, differentiation, development, and apoptosis . Recently, it has been reported that cancer tissues are a vital source of miRNAs, and miRNAs can function as tumor oncogenes or suppressors . Current researches suggest that miRNA provides a novel molecular approach to understand HCC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of endogenous, small non-coding RNAs, microRNAs (miRNAs) can regulate gene expression by repressing translation or promoting mRNA degradation. 6 Besides, miRNAs play roles in various cellular processes, including cell proliferation, differentiation, development, and apoptosis. 7 Recently, it has been reported that cancer tissues are a vital source of miRNAs, and miRNAs can function as tumor oncogenes or suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, miR‐490‐3p also becomes important as it has been shown to be downregulated in multiple tumors including gastric cancer, ovarian, osteosarcoma, breast, colorectal and endometrial cancer where it has been shown to play a tumor suppressive role . In contrast, its upregulated expression has also been reported in lung and hepatocellular carcinoma where it functioned as an oncomiR . We also report for the first time that miR‐490‐3p in GBM induces tumor suppression via inhibiting cell proliferation, anchorage independence, migration, EMT and spheroid‐forming ability and by inducing apoptosis in GBM cells.…”
Section: Discussionmentioning
confidence: 75%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] In contrast, its upregulated expression has also been reported in lung and hepatocellular carcinoma where it functioned as an oncomiR. 32,33 We also report for the first time that miR-490-3p in GBM induces tumor suppression via inhibiting cell proliferation, anchorage independence, migration, EMT and spheroid-forming ability and by inducing apoptosis in GBM cells. Also, previously reported EZH2 mediated promotion of GBM cell migration 3 and downregulation of miR-490-3p (as per our study) indicates EZH2 role in promoting GBM cell migration at least in part via the suppression of miR-490-3p.…”
Section: Discussionmentioning
confidence: 92%